Psychological correlates of performance-enhancing drug use: Emotional, cognitive, and social functioning in long-term and short-term users - Çınaroğlu, Metin; Yılmazer, Eda (Frontiers in Psychiatry, 2025)
IntroductionPerformance-enhancing drug (PED) use—particularly anabolic–androgenic steroids (AAS)—has expanded from competitive sport into mainstream fitness settings. Although PED use is associated with emotional, cognitive, and social difficulties, less is known about how duration of use or psychosocial factors shape these outcomes. Understanding these dynamics is essential for identifying individuals at greater risk for psychological impairment.MethodsA total of 285 adult gym-goers (87 long-term users, 95 short-term users, 103 non-users) completed validated measures of depression (BDI-II), anxiety (BAI), muscle dysmorphia (MDDI), self-efficacy (GSE), social support (MSPSS), and social functioning (SASS), along with the Stroop test assessing executive function. Group comparisons, multiple regressions, and PROCESS-based mediation and moderation analyses were conducted, controlling for demographic covariates.ResultsLong-term PED users reported significantly higher depression, anxiety, and muscle dysmorphia than short-term users and non-users, and showed poorer Stroop interference performance. Mediation analysis revealed that depression and anxiety partially explained the link between PED use and poorer social functioning. Moderation results indicated that stronger self-efficacy and higher perceived social support buffered depressive and anxious symptoms among users.DiscussionChronic PED use is associated with heightened emotional distress and reduced executive functioning, which in turn contribute to impaired social functioning. However, psychosocial resources such as self-efficacy and social support may mitigate these adverse effects. These findings underscore the need for routine psychological assessment and the development of supportive, prevention-oriented interventions for individuals engaged in PED use.